Cover Picture: A Prototypical Small‐Molecule Modulator Uncouples Mitochondria in Response to Endogenous Hydrogen Peroxide Production (ChemBioChem 8/2013). Issue 8 (17th May 2013) - McQuaker, Stephen J.; Quinlan, Casey L.; Caldwell, Stuart T.; Brand, Martin D.; Hartley, Richard C.
<x xml:space="preserve">Abstract</x> The cover picture shows a new approach to dealing with the dysfunctional mitochondria (red) that produce excess reactive oxygen species (ROS) as a result of a high membrane potential. Excess ROS leads to the oxidative stress evident in almost all age‐related diseases and which is implicated in the process of ageing itself. The new approach is to correct the process of ROS generation, giving well‐behaved mitochondria (green), rather than simply mopping up the ROS. A prototypical prodrug MitoDNP‐SUM offers hope of this: it accumulates selectively in mitochondria and releases an uncoupler, which would lower the membrane potential, in response to endogenous ROS. For more details see the paper by R. Hartley et al. on p. 993 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>